Strategi Bhabinkamtibmas Polsek Jambangan Untuk Meningkatkan Peran Serta Masyarakat Guna Pemeliharaan Kamtibmas di Wilayah Kecamatan Jambangan - Pitajeng, Laras Ayu; Ismail; Nurany, Fierda (Universitas Bojonegoro, 2024)
This study aims to determine the Bhbinkmtibmas strategy in increasing community participation in maintaining security and order in the Jambangan District area. Because from the end of 2022 to the beginning of 2023 several cases were recorded in Jambangan District, namely persecution, disputes, unpleasant acts, theft, alcohol and gambling.The research method used is a type of qualitative research. Informants in this study were Bhbinkamtibmas Polsek Jambangan, Bhbinsa Polsek Jambangan, Staff of the Jambangan Village and the Jambangan Village community. Data collection techniques in this study were interviews and documentation. Data analysis techniques used in this study are data reduction, data exposure and decision making. The results of this research show that: (1) The strategies implemented by Bhbinkamtibmas to increase community participation in maintaining security and safety include the partiality approach strategy, strategy for sharing participation and strategies for granting limited authority, (2) Obstacles faced by Bhbinkamtibmas in fostering security in the community include the competence of Bhabinkamtibmas services, community understanding, facilities and infrastructure, (3) Efforts carried out by Bhbinkamtibmas to maintain security and order in the surrounding environment, namely Pre-Efforts emtive, Preventive Efforts and Repressive Efforts. It is better for every community, regardless of social status, to be aware of the importance of maintaining security and order in the environment, to be able to maintain kamtibmas